The interactive nature of business development services in the relationship between external business environment and firm performance - Okeyo, Washington (Advances in Social Sciences Research Journal, 2015)
This study focused on the interaction of business development services in the external business environment and firm performance relationship. The study adopted a cross sectional survey design on 800 small and medium manufacturing enterprises in Kenya. Data were collected using structured questionnaires from a sample of 150 enterprises and 64% responded. The instrument was tested for reliability using Cronbach’s approach while data was tested for normality and homoscedasticity before applying regression methods to test hypotheses. Principal component analysis was used to determine suitable predictor variable factors for regressions. The study established that external business environment has a significant positive but partial effect on performance and that business development services partially mediate this relationship. The study recommends that small and medium enterprises should embrace business development services practices to leverage the effect of external business environment on their performance. Key words: External, business, environment, services, mediation, small, medium, enterprises, performance